STRATEGI BERTAHAN HIDUP DAN HUKUM ISLAM: ANALISIS TERHADAP NIAT ANTARA IBADAH PUASA DAN KETERPAKSAAN KARENA KEMISKINAN - Nabila Nur Aini; Citra Azra Amalia; Shelomitha Azalia Widyaningrum; Arie Sukanti Siagian; Baidhowi Baidhowi (CV. Denasya Smart Publisher, 2025)
Poverty, which arises as a result of unequal development, has become a serious issue for many communities. Economic hardship often compels individuals to justify any means necessary to achieve their goals, even at the cost of violating moral values. This condition not only triggers criminal behavior but also contributes to the decline of morality, as people may neglect social and religious norms in order to survive. As a multidimensional problem, poverty generates various social issues. Under economic pressure, individuals working as laborers, small traders, or low-income employees are sometimes driven to deviant acts such as theft, robbery, or even prostitution. Such circumstances also influence the practice of religious duties, as some people tend to neglect religious and moral obligations in order to fulfill their basic needs. This study aims to examine the relationship between fasting as a religious obligation and the sense of compulsion brought about by economic difficulties. Miles & Huberman identify the main causes of poverty as low levels of education, weak work ethic, and limited employment opportunities. Consequently, religious practices such as prayer, fasting, and other Islamic activities are often performed inconsistently. From the perspective of Islamic law, this phenomenon reflects a shift in intention: acts of worship that should be based on sincerity may instead be carried out under compulsion due to economic pressure. Thus, poverty fosters survival strategies that weaken the quality of religious observance and create a dilemma between genuine devotion and compulsion in performing fasting